Effect of different solvents on antioxidant activity of Euphorbia hirta L. extract - Nyoman Suarjana; Made Nyandra; Ni Putu Widya Astuti; Ni Made Kurniati; Ni Luh Utari Sumadewi; I Made Wisnu Adhi Putra; Nurrahman Andrianto (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
Euphorbia hirta L. is a species of plant renowned for its antioxidant properties. However, the optimal solvent for extracting these bioactive compounds to maximize antioxidant activity had not been systematically identified and compared. Previous knowledge suggested that solvent choice affects yield and efficacy; however, there was a lack of conclusive, comparative data specifically for E. hirta extracts using different solvents. The focus of this work was to investigate how different solvents affected the content of phenolics and flavonoids, as well as the antioxidant effect of E. hirta extract. The aerial part of E. hirta powder was extracted with ethanol, ethyl acetate, and n-hexane to obtain the crude extracts. Folin-Ciocalteu reagent and AlCl3 solution were used to assess the total phenolic and flavonoid contents, respectively. The ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) techniques were used to assess antioxidant activity. The total content of phenolics and flavonoids of E. hirta ethanol extract (127.827 ± 2.609 mg GAE/g extract and 28.507 ± 0.464 mg QE/g extract, respectively) was substantially higher than that of the other extracts (p<0.0001). The findings of the FRAP test exhibited that the E. hirta ethanol extract (48.009 ± 1.873 mg AAE/g extract) had a substantially greater reducing power value (p<0.0001) in comparison to other extracts. The ethanol extract of E. hirta had a considerably lower IC50 value (6.154 ± 0.063 ppm and 9.429 ± 0.183 ppm for DPPH and ABTS assays, respectively, with p<0.0001) than the other extracts. This study found that solvent polarity had a substantial influence on the antioxidant activity of E. hirta extracts, with ethanol being an optimal solvent for the extraction procedure.